Medidas de autocuidados en los paciente diabético del Centro de Salud “10 de noviembre” del Cantón Ventanas de La Provincia de Los Ríos. Periodo mayo- septiembre 2019. - Sipion Guerrero, Mayerlhy Katiusca (2019)
Diabetes is a chronic non-communicable disease is caused when the pancreas does not generate enough insulin to the organs affects everyone regardless of age sex color and race there are 3 types of diabetes. This disease is caused by several factors such as sedentary lifestyle, excessive consumption of salt and trans fat bad eating habits and alcohol consumption and also hereditary. By not taking care with responsibility, future complications may occur since self-care are the actions that people accept in favor of their own health without medical supervision. For these reasons, the following report worked with 60 people affected by diabetes, the results will be detailed below for which we have proposed a proposal to prevent future complications. The authors want this report to be liked by the group and leave any doubt at your disposal anticipating their thanks.